2019
DOI: 10.3390/su11123380
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Drivers of Farm Diversification Among U.S. Fruit and Vegetable Operations

Abstract: Diversification of an agricultural operation’s crop mix is considered an environmental and financial management strategy. Environmentally, crop diversification can stabilize the ecosystem via the introduction of biodiversity, allowing for more rapid response to physical and social changes. Economically, crop mix diversification can mitigate risk. Though there are environmental and economic benefits of crop diversification, little economic work has been conducted on crop diversification outside of the row crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Interestingly, the same marketplace attributes influencing customers to purchase fruits at local markets are those deterring them to purchase at chain stores. Our findings are consistent with those of Archambault et al (2020), Kumar and Smith (2018), and Lancaster and Torres (2019), who reported that friendliness and access to local fruits entice customers to purchase at local markets. Initiatives like "know your farmer, know your food" efforts to support local farmland and local economy and local food programs at the state and community levels seem to be encouraging the demand for local foods.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, the same marketplace attributes influencing customers to purchase fruits at local markets are those deterring them to purchase at chain stores. Our findings are consistent with those of Archambault et al (2020), Kumar and Smith (2018), and Lancaster and Torres (2019), who reported that friendliness and access to local fruits entice customers to purchase at local markets. Initiatives like "know your farmer, know your food" efforts to support local farmland and local economy and local food programs at the state and community levels seem to be encouraging the demand for local foods.…”
Section: Discussionsupporting
confidence: 93%
“…To gain a better understanding of the changes in consumer demand, several researchers have investigated what drives consumers to purchase and consume fresh fruits. Researchers have reported fresh fruit purchases can be driven by product attributes and consumer attitudes (Bir et al, 2019;Canova et al, 2020;Lancaster and Torres, 2019;Massaglia et al, 2019;Torres et al, 2020;Witzling and Shaw, 2019). For example, consumers are increasing their knowledge of the benefits of eating fresh fruits (Canova et al, 2020) and valuing the experience of eating fresh fruits (Torres et al, 2020).…”
mentioning
confidence: 99%
“…On the contrary, the negative effect between communication costs and local market outlet choice could be due to proximity of a farm to the market, which is also within vicinity of the buyers and eases communication through word of mouth between farmers and buyers thereby increasingpeach sale at relatively low advertisement costs. Information spreading by word of mouth is equally important in the flow of information (Lancaster and Torres, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies confirm that farmers use different strategies to mitigate expected risks. In addition to financial instruments, farmers respond to these events via crop diversification, which, in addition to economic benefits, also brings environmental benefits [65][66][67].…”
Section: Similarities Among Slovak Regions With Respect To the Development Of Sown Areas Of Selected Cropsmentioning
confidence: 99%